Functional aspects of salivary nitric oxide synthase of Rhodnius prolixus (Hemiptera, Reduviidae) and nitric oxide trafficking at the vector-host interface. Issue 1 (December 2017) - Paim, Rafaela; Nascimento, Bruno; Nascimento, Ana; Pacheco, Dimitri; Soares, Adriana; Araujo, Ricardo; Sant'Anna, Mauricio; Pessoa, Grasielle; Gontijo, Nelder; Pereira, Marcos
Abstract Rhodnius prolixus expresses nitric oxide synthase (NOS) in the cytosol of the salivary gland (SG) cells. The NO produced is stored in the SG lumen bound to NO-carrier haemeproteins called nitrophorins (NPs). NPs bind tightly to NO in the acidic SG lumen, but release NO when the pH becomes high, e.g., at the host skin (pH 7.4). NO elicits potent and transient relaxation of vascular smooth muscle. Here, we investigated the role of salivary NO in theR .prolixus feeding behaviour and the salivary vasodilator activity of the host microcirculation. NOS knockdown inR .prolixus changed the SG colour, decreased the number of NO-loaded NPs and caused impairment of feeding performance. When salivary gland extracts (SGEs) were obtained from NOS- and NPs-knockdown insects and prepared in pH 5.0 solution and injected (i.v.) into mice via the tail vein, no vasodilation was observed, whereas SGEs from control insects caused long-term venodilation in the mouse skin. SGs disrupted directly in PBS (pH 7.4) containing BSA produced long-term vasodilation compared to the controls without BSA due to the possible formation of nitroso-albumin, suggesting that host serum albumin extends the NO half-life when NO is injected into the host skin by triatomine during their blood-feeding.